La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Centre de recherche interuniversitaire sur la littérature et la culture au Québec [CRILCQ], 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Black Women Dancers, Jazz Culture, and “Show Biz”: Recentering Afro-Culture and Reclaiming Dancing Black Bodies in Montréal, 1920s–1950s - Jabouin, Emilie (Canadian Journal of History, 2021)
The documentary Show Girls, directed by Meilan Lam, makes an unprecedented contribution to the history of jazz and Black women jazz dancers in Montréal, Quebec, and to the conversation of jazz in Canada. Show Girls offers a glimpse into the lives of three Black women dancers of the 1920s–1950s. This essay asks what the lives of Black women dancers were like and how they navigated their career paths in terms of social and economic opportunities and barriers. I seek to better understand three points: (1) the gap in the study of jazz that generally excludes and/or separates dance and singing from the music; (2) the use of dance as a way to commercialize, sell, and give visual and conceptual meaning to jazz; (3) the importance of the Black body and the role of what I would define as “Afro- culture” in producing the ingenious and creative genre of jazz. My study suggests there is a dominant narrative of jazz, at least in academic literature, that celebrates one dimension of jazz as it was advertised in show business, and that bringing in additional components of jazz provides a counternarrative, but also a restorative, whole and more authentic story of jazz and its origins. More specifically, by re- exploring jazz as a whole culture that relies on music, song, and dance, this essay explores three major ideas. First, Black women dancers played a significant role in the success of jazz shows. Second, they articulated stories of self, freedom, and the identity of the New Negro through jazz culture and dance. Third, Black women’s bodies and art were later crystallized into images that further served to sell jazz as a product of show business.

Dick Montgomery et la personnification féminine afrodescendante en Amérique du Nord, 1935-1960 - Jacques, Raphaël (Histoire Engagée, 2021)

Sounding the Arctic in Chantal Bilodeau’s Climate Change Plays - Balestrini, Nassim W. (Nordic Theatre Studies, 2020)
Quebec-born playwright Chantal Bilodeau has been responding to the challenges of dramatizing anthropogenic climate change by developing an eight-part Arctic Cycle, each play of which is set in one of the nations that claims Arctic territory. Sila (2014) immerses audiences into a complex network of humans, animals, and mythical beings crisscrossing the Canadian Arctic. These movements circle around the Inuit concept of sila, which is the life-giving force of breath and voice. Thus, the sonic world of Sila focuses on voices speaking words, on performance poetry, and on the sounds of breath and wind. Bilodeau’ s second Arctic Cycle play, Forward (2016), addresses the long-term impact of Fridtjof Nansen’s polar exploration of the 1890s on Norway’s economy and society. In terms of sound, Forward features multiple musical performances rangingfrom traditional songs to European opera arias and Lieder to contemporary Norwegian electro-pop. The sonic features of both plays stress interdependence across time, space, as well as (non-)human, earthly, and metaphysical realms. Sila and Forward address climate change in a non-universalizing manner which promotes a heterarchical (rather than hierarchical) aesthetic fit for a growing awareness of planetary relationality.
Keywords: Theory and practice

Tuning a Room: Designs for Hearing According to Nancy Tobin - Rewa, Natalie (Canadian Theatre Review, 2020)
In this review, I discuss the architectonics of sound composition according to sound artist and designer Nancy Tobin. This chapbook advocates for a comprehensively integrated presence of a sound artist in the processes of rehearsal and espouses a dramaturgy of hearing. Tobin’s distinction between hearing and listening gives forth onto a series of self-studies of her experience of spatial and temporal arrangements presented in the form of e-mails to mentees. Her appreciation for the acoustics of the performance space extends to the composition of sound to be heard (on occasion as boldly interventionist) and the technologies of broadcasting it: the choice and placement of speakers, as well as their interaction with the performers. Tobin argues for a definition of sound composition for performance as a complex collaboration with the production—curatorial in terms of the space of ephemerality. My review concurs with the efficacy of her approach by my recognition of the moments in productions that have remained as some of the most memorable of my theatregoing.
Keywords: Nancy Tobin; acoustic space; rehearsal processes; sonic/acoustic dramaturgy; sound artist; speaker specifications and broadcasting sound